Plays for Children - Ed. Rose, Helen (Faber and Faber Ltd, 2000)
Indigo Mill by Nick Fisher, Body Talk by Andy Rashleigh, Odessa and the Magic Goat by John Agard and Little Victories by Shaun Prendergast - this is a collection of plays for children of primary school age. They encompass topics from Victorian weavers to European folklore and magic.
Keywords: Juvenile literature-Fiction